Розвиток монокарпічного пагона Мiscanthus sinensis Anderss. при інтродукції в Лісостепу та на Поліссі України - Scherbakova, T.O.; Rakhmetov, D.B. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2015)
The morphogenesis of Miscanthus sinensis Anderss. monocarpic shoot in conditions of the introduction of the Forest- Steppe and Polissya of Ukraine has been described. Five phases of shoots morphogenesis (phase of developing bud (embryonic phase), phase of unfolding of squama and rhizomatous growth, phase of the developing inflorescence and stem, flowering phase and phase of secondary rhizomatous activities) have been identified. Terms of phase duration and morphological characteristics of shoots at every stage of development have been found. It was established that the duration of the phases of developing bud and unfolding of squama and rhizomatous growth is 24 months. The formation of M. sinensis shoot apexes is from the II–III decade of October to the II–III decade of April. Their differentiation is necessary on I–III decade of November (for shoot apex which was formed in October) and I–III decade of May (for shoot apex which was formed in April). The unfolding of the first assimilation leaves and formation of rudimentary inflorescences was observed in II–III decade of October for winter shoots and in II–III decade of April next year for spring shoots. M. sinensis plants have postreproductive tillering.